Application of dynamic contrast enhanced ultrasound in the assessment of kidney diseases. Issue 1 (January 2021) - Selby, Nicholas M.; Williams, John P.; Phillips, Bethan E.
Abstract : Purpose of review: Many forms of acute and chronic disease are linked to changes in renal blood flow, perfusion, vascular density and hypoxia, but there are no readily available methods to assess these parameters in clinical practice. Dynamic contrast enhanced ultrasound (DCE-US) is a method that provides quantitative assessments of organ perfusion without ionising radiation or risk of nephrotoxicity. It can be performed at the bedside and is suitable for repeated measurements. The purpose of this review is to provide updates from recent publications on the utility of DCE-US in the diagnosis or assessment of renal disease, excluding the evaluation of benign or malignant renal masses. Recent findings: DCE-US has been applied in clinical studies of acute kidney injury (AKI), renal transplantation, chronic kidney disease (CKD), diabetic kidney disease and to determine acute effects of pharmacological agents on renal haemodynamics. DCE-US can detect changes in renal perfusion across these clinical scenarios and can differentiate healthy controls from those with CKD. In sepsis, reduced DCE-US measures of perfusion may indicate those at increased risk of developing AKI, but this requires confirmation in larger studies as there can be wide individual variation in perfusion measures in acutely unwell patients. Recent studies in transplantation have not provided robust evidence to show that DCE-US can differentiate between different causes of graft dysfunction, although it may show more promise as a prognostic indicator of graft function 1 year after transplant. DCE-US can detect acute haemodynamic changes in response to medication that correlate with changes in renal plasma flow as measured by para-aminohippurate clearance. Summary: DCE-US shows promise and has a number of advantages that make it suitable for the assessment of patients with various forms of kidney disease. However, further research is required to evidence its reproducibility and utility before clinical use can be advocated.